Dr. Ursula Martius Franklin (1921-2016) - Frize, Monique (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2019)
Ursula Franklin was born in Germany in 1921 and moved to Canada in 1949 after surviving the Holocaust. She joined the University of Toronto’s Department of Metallurgy and Materials Science in 1967, and became the institution’s first female “university professor” in 1984. This memoriam recounts her influence on the author, among the many others Ursula Franklin touched during her remarkable life and career.